The Impact of Timber Legality Verification System (SVLK) on Indonesian Plywood Export Market - Notonegoro, Dwi Putro (Universitas Negeri Malang, 2018)
This paper estimates the regulation affects in the plywood export market, not only on the quantity exported but also on the revenue earned from this product. Using panel data of this market from 2000 to 2014 and involving 58 countries as trading partner, gravity model which has been used in many studies of international trade will be adapted. Three models which are used in this study, which are pooled least square, fixed and random effect model, finds an indication that quantity exported and revenue earned after the implementation of the regulation is less than before. In pooled regression model, the quantity and revenue from plywood export decreased more than 95 %, in addition, fixed and random effect model shows similar result with the pooled regression model.